2017
DOI: 10.1123/ijspp.2015-0484
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Simple Method for Measuring Force-Velocity-Power Profile in Countermovement Jump

Abstract: These results suggest that the simple method presented here is valid and reliable for computing CMJ force, velocity, power, and F-v profiles in athletes and could be used in practice under field conditions when body mass, push-off distance, and jump height are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 26 publications
9
108
3
2
Order By: Relevance
“…The relative difference between actual and optimal F-v profiles for a given individual represents the magnitude and the direction of the unfavorable balance between force and velocity qualities (i.e., force-velocity imbalance, FV imb in %), which makes possible the individual determination of force or velocity deficit. The actual individual F-v profile and P max can be easily determined from a series of loaded vertical jumps (Samozino et al, 2008, 2014; Jiménez-Reyes et al, 2014, 2016; Giroux et al, 2015, 2016), while the optimal F-v profile can be computed using previously proposed equations based on a biomechanical model (Samozino et al, 2012, 2014). For a given P max , vertical jump performance has been shown to be negatively correlated to FV imb , which supports the importance of considering this individual characteristic in addition to P max when designing training programs to improve ballistic performance (Samozino et al, 2012, 2014; Morin and Samozino, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The relative difference between actual and optimal F-v profiles for a given individual represents the magnitude and the direction of the unfavorable balance between force and velocity qualities (i.e., force-velocity imbalance, FV imb in %), which makes possible the individual determination of force or velocity deficit. The actual individual F-v profile and P max can be easily determined from a series of loaded vertical jumps (Samozino et al, 2008, 2014; Jiménez-Reyes et al, 2014, 2016; Giroux et al, 2015, 2016), while the optimal F-v profile can be computed using previously proposed equations based on a biomechanical model (Samozino et al, 2012, 2014). For a given P max , vertical jump performance has been shown to be negatively correlated to FV imb , which supports the importance of considering this individual characteristic in addition to P max when designing training programs to improve ballistic performance (Samozino et al, 2012, 2014; Morin and Samozino, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The relative influences of hPO, Pmax and Fv profile on SJ performance are summarized in the following equation, that has been validated experimentally [19,26]: In this equation, hmax is the maximal possible SJ height reached with an optimal Fv profile SFvopt. Note that these demonstrations have been initially published using SJ as the jump modality, but subsequent works by Jimenez-Reyes et al have shown that similar conclusions could be drawn for the CMJ modality [7]. A practical summary of the above-mentioned theoretical points is that the relationship between SJ or CMJ height is clearly confounded by individual anthropometrical and physiological factors inherent to each athlete tested.…”
Section: 3mentioning
confidence: 77%
“…This method, based on macroscopic modelling of body mass displacement and the associated mechanical external work, requires only body mass, hPO and jump height. The initial reliability and concurrent validity was tested against reference force plate measurements [8], and was confirmed in subsequent studies from other authors, including additional load conditions and application to CMJ [7,46,47]. In this method, the mean power produced during a jump was computed as:…”
Section: 3mentioning
confidence: 83%
See 2 more Smart Citations